Mariposas en la calle Carmen - Brown, Monica, 1969-; Brown, Monica, 1969-; Ward, April; Ventura, Gabriela Baeza (Houston, TX : Pinata Books, 2007)
While she and her classmates wait for the caterpillars they are raising to be transformed into Monarch butterflies, Julianita's grandfather tells her about the annual migration of these butterflies to his hometown in Mexico.
Mientras la nina y sus companeros de la clase esperan para las orugas terminan convirtiendose en mariposas monarcas, el abuelo de Julianita le cuenta sobre la migracion anual de estas mariposas monarcas a su pueblo en Mexico.
890
Accelerated Reader
Keywords: Monarch butterfly -- Juvenile fiction; Butterflies -- Juvenile fiction; Grandfathers -- Juvenile fiction; Mexican Americans -- Juvenile fiction; Hispanic Americans -- Juvenile fiction; Hispanoestadounidenses -- Novela juvenil; Spanish language materials -- Bilingual -- Juvenile literature; Materiales en espanol -- Bilingue -- Literatura juvenil; Mexicano-americanos -- Novela juvenil; Mariposa monarca -- Novela juvenil; Mariposas -- Novela juvenil; Abuelos (Hombres) -- Novela juvenil; #OwnVoices - Latinx